The effects of public funding on agricultural performance and environmental degradation in Ghana: Case studies of three arboriculture value chains (Cocoa, Cashew and Mango) - Yaya Koloma; Juste Some (ZBW – Leibniz Information Centre for Economics, 2023)
This paper examines the effects of public financing devoted to agriculture on the performance of the agriculture sector and on the environmental degradation in Ghana over the period 1996-2019. The paper particularly focuses on three tree crops value chains, namely cashew, cocoa and mango sub-sectors. The agriculture performance is measured by the value added. The environmental degradation is measured by the greenhouse emissions from agriculture. The empirical methodology is based on a multivariate econometric approach, in particular a VAR model in a form of error correction that considers the long-term relationships (cointegration) between variables. The results from the impulse-response functions indicate that public financing significantly improves agricultural performance but with mixed impacts on environmental quality. It helps improve agricultural performance by increasing agricultural value added and agricultural productivity. However, this support tends to have a negative impact in terms of CO2 emissions in Ghana. The policy implications suggest that the increase in support to the agricultural sector is highly commendable and should be strengthened for the three trees crops, but policymakers should consider the potential negative impact of the financing on carbon dioxide emissions. To this end, while for mango a few non-financial measures seem necessary, for cocoa and cashew, substantial non-financial resources are required to make these crops more climate or environmentally sensitive, through incentives and awareness. This means encouraging use of innovative tools on farms, including climate smart agriculture methods to make these crops less degrading for the quality of the environment in Ghana.
Keywords: Q14; Q56; Q18; 330; Public Financing; tree crops value chains; Environmental degradation; Ghana; VAR models